Infants, toddlers, and families in poverty : research implications for early child care - Odom, Samuel L.; Pungello, Elizabeth Puhn; Gardner-Neblett, Nicole (Guilford Press, 2012)
Identifying factors related to poverty that affect infants, toddlers, and their families, this book describes promising early child care and intervention practices specifically tailored to these children and families' needs. Leading authorities from multiple disciplines present cutting-edge research and discuss the implications for practice and policy. Contributors review salient findings on attention, memory, language, self-regulation, attachment, physical health, family processes, and culture. The book considers the strengths and limitations of existing early intervention services for diverse populations and explores workable ways to improve them.